Aneuploidy: the impact of chromosome imbalance on nuclear organization and overall genome expression. Issue 1 (23rd March 2016) - Hervé, B.; Coussement, A.; Gilbert, T.; Dumont, F.; Jacques, S.; Cuisset, L.; Chicard, M.; Hizem, S.; Bourdoncle, P.; Letourneur, F.; Dupont, C.; Vialard, F.; et al.
Abstract : The organization and dynamics of chromatin within the interphase nucleus as chromosome territories (CTs) and the relationship with transcriptional regulation are not fully understood. We studied a natural example of chromosomal disorganization: aneuploidy due to trisomies 13, 18 and 21. We hypothesized that the presence of an extra copy of one chromosome alters the CT distribution, which perturbs transcriptional activity. We used 3D‐FISH to study the position of the chromosomes of interest (18 and 21) in cultured amniocytes and chorionic villus cells from pregnancies with a normal or aneuploid karyotype. We studied the volumes of nuclei and CTs in both conditions and performed a compared transcriptome analysis. We did not observe any differences between euploid and aneuploid cells in terms of the radial and relative CT positions, suggesting that the same rules govern nuclear organization in cases of trisomy. We observed lower volumes for CTs 18 and 21. Overall genome expression profiles highlighted changes in the expression of a subset of genes in trisomic chromosomes, while the majority of transcriptional changes concerned genes located on euploid chromosomes. Our results suggest that a dosage imbalance of the genes on trisomic chromosomes is associated with a disturbance of overall genomic expression. Abstract :